2017 IEEE Asia Pacific Microwave Conference (APMC) 2017
DOI: 10.1109/apmc.2017.8251649
|View full text |Cite
|
Sign up to set email alerts
|

Differential common base TIA with 56 dB Ohm gain and 45 GHz bandwidth in 130 nm SiGe

Abstract: In this work we present two transimpedance amplifier (TIA) circuits designed for fibre optical interconnect systems. We compare a common base (CB) topology with a common emitter (CE) shunt-shunt feedback topology in terms of frequency response, power consumption, noise and input impedance. The two TIAs are designed on a 130nm InP DHBT technology from Teledyne Scientific Company (TSC) with an ft/fmax of 520 GHz/1.15 THz and are measured in the frequency and time domains. They exhibit a TI-gain of 42 dBΞ© with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Hence, a TIA with low input resistance reduces the time constant and significantly increases the receiver bandwidth. Circuits with low input resistance, such as the common base (CB) [3,4] and the regulated cascode (RGC) TIAs [5], originally proposed for earlier generations of optical fibre communication systems, are more recently found to be highly attractive for use in VLC systems [6][7][8][9]. For example, our recent work in [6] reports a specially designed modified RGC TIA for largearea photodiodes, achieving a bandwidth of 200 MHz at 2 kΩ with an equivalent C pd of 300 pF.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a TIA with low input resistance reduces the time constant and significantly increases the receiver bandwidth. Circuits with low input resistance, such as the common base (CB) [3,4] and the regulated cascode (RGC) TIAs [5], originally proposed for earlier generations of optical fibre communication systems, are more recently found to be highly attractive for use in VLC systems [6][7][8][9]. For example, our recent work in [6] reports a specially designed modified RGC TIA for largearea photodiodes, achieving a bandwidth of 200 MHz at 2 kΩ with an equivalent C pd of 300 pF.…”
Section: Introductionmentioning
confidence: 99%
“…The eventual benefit of such a low noise TIA is the possibility of widening the bandwidth for higher data rate applications. Traditionally, the low noise TIA were implemented in SiGe HBT [1], CMOS [2], InP DHBT [3] with SiGe HBT based TIA reaching up to 5.5 𝑝𝐴 βˆšπ»π‘§ ⁄ of input referred noise. This is the state-of-the-art in these technologies for TIA circuits.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the vast majority of reports, the designs involve photodiode capacitances (c pd ) of typically just a few picoFarads (pF), which is particularly low in comparison to the values encountered in visible light communication (VLC) systems. Designs have been reported that utilise key bandwidth extension techniques, such as low input impedance amplifiers featuring common base (CB) [2,4,5] or regulated cascode (RGC) [6,7] configurations. Different realisations of the RGC have been reported, with some featuring additional bandwidth optimisation techniques such as inductive [8] and capacitive peaking [9].…”
Section: Introductionmentioning
confidence: 99%